DIGITALIZATION MANAGEMENT: ENHANCED TOURIST ENGAGEMENT BAH KOH SAMED ISLAND, CHUMPHON PROVINCE, THAILAND - Pernandus Simanullang (FKIP, Universitas Palangka Raya, 2023)
The issue of tourism governance in Bah Koh Samed is very important to find a solution, so that tourists can have a good experience and local communities can utilize tourism as a sustainable source of income. Good governance involves an online ticketing system and digitalization strategies to strengthen the image of tourism. This case study focuses on finding alternatives to Koh Samed as a creative tourism destination that not only attracts more tourists but also restores Koh Samed sustainably. A new tourism model can be created with the development of digitalization technology for Koh Samed Bah Island operations ranging from ticket validation, ticketing solutions, ticket point of sale, voucher codes, communication, and partnership to increase visitors as well as revenue. Through increasing the attraction of art activities, it can be directly listed on the Koh Samed Bah Island website and links. Offer and develop creative spaces for Bah Koh Samed Island that need to increase the art network through digitalization management. The main object of this research focuses on the role of tourists, local communities, and stakeholders through digitization management, and the networking of each destination location by utilizing the arts and cultural ecosystem. This research method uses descriptive qualitative methods, data collection, interviews, and documentation. Data collection is not only by interacting with each other, but written and in-depth. Then automatic verification from each stakeholder will help answer the obstacles that exist during or before. Then proceed with data analysis which is used to answer research problems by testing hypotheses through the data that has been obtained. Data analysis instruments use SWOT analysis as an initial basis for knowing weaknesses and strengths. Then in-depth analysis to increase visitors through increasing the attraction of art activities and developing digitalization technology.